Religiusitas Post-Dogmatik (Membangun Transendensi Sosial Humanistik) - Haqqul Yaqin (HUMANISTIKA : Jurnal Keislaman, 2017)
In the long history of his travels, religion is often stuck in a puddle interests of its adherents, so that the values of the religious ideal stuck in a subjective vested interest for short-term interests. Understanding and assumptions that are based on the principles and norms of religion is so rigid and simplistic, as well as enforcement efforts away from the values of divine and human. More dogmatic religion appeared as an attempt to interpret the dominance of truth. And if religion wants to get back to nature as the disseminator of peace must be constructed of thinking and understanding beyond the dogma, namely the religious mindset that is not frozen in a rigid understanding of the text. Postdogmatik religious ideas and alternate bids actually attempts to spread the religion rahmatan lil Alamin.